2023
DOI: 10.3390/toxics11030225
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Microplastics Induced Ovarian Toxicity in Juvenile Rats Associated with Oxidative Stress and Activation of the PERK-eIF2α-ATF4-CHOP Signaling Pathway

Abstract: Numerous reports confirm that microplastics exposure could induce reproductive toxicity in mammals. However, the effects of microplastics exposure during juveniles on ovarian apoptosis through oxidative and endoplasmic reticulum (ER) stresses remains unclear, which is the focus of our study. In the present study, female rats (4 weeks old) were exposed to polystyrene microplastics (PS-MPs, 1 μm) at different dosages (0, 0.5, and 2.0 mg/kg) for 28 days. Findings revealed that 2.0 mg/kg of PS-MPs distinctly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Polystyrene was the polymer that was most frequently used in studies on how MPs affected RS stress [145,[148][149][150]. Rats, mice, and fish were used in these analyses [145,[148][149][150].…”
Section: Effect Of Mps On An Endoplasmic Reticulummentioning
confidence: 99%
See 2 more Smart Citations
“…Polystyrene was the polymer that was most frequently used in studies on how MPs affected RS stress [145,[148][149][150]. Rats, mice, and fish were used in these analyses [145,[148][149][150].…”
Section: Effect Of Mps On An Endoplasmic Reticulummentioning
confidence: 99%
“…Polystyrene was the polymer that was most frequently used in studies on how MPs affected RS stress [145,[148][149][150]. Rats, mice, and fish were used in these analyses [145,[148][149][150]. It was discovered that PS (1 µm, 2.0 mg/kg) caused young rats to express genes linked to ER stress (PERK, eIF2α, ATF4, and CHOP) [150].…”
Section: Effect Of Mps On An Endoplasmic Reticulummentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that MPs can cause reproductive harm in animals [168,169]. 2.0 mg/kg of polystyrene microplastics (PS-MPs) significantly raised the atretic follicle ratio in the ovary and significantly decreased blood levels of estrogen and progesterone [168].…”
Section: Mps and Nps In The Ovarymentioning
confidence: 99%
“…Studies have found that MPs can cause reproductive harm in animals [168,169]. 2.0 mg/kg of polystyrene microplastics (PS-MPs) significantly raised the atretic follicle ratio in the ovary and significantly decreased blood levels of estrogen and progesterone [168]. Furthermore, the activity of oxidative stress markers such as superoxide dismutase and catalase were significantly decreased [168], indicating that PS-MPs exposure could induce ovarian injury associated with oxidative stress.…”
Section: Mps and Nps In The Ovarymentioning
confidence: 99%